Effects of Puncture Vine Plant (Tribulus Terrestris L.) Extract on All Larval Stages of Mosquito, Culex Pipiens (Diptera: Culicidae) - Hassan, Sara Ayoub; Al-Chalabi, Badia'a Mahmoud (Science Journal of University of Zakho, 2023)
The existing research was conducted in Duhok city to investigate the biological impact of extracting secondary chemical compounds from punctured vine plants (Tribulus terrestris L.) on the mortality of all larval stages of (Culex pipiens). Bioassay experiments were carried out by using solvent extraction methods and different concentrations (0.1,0.3,0.5,0.7) mg/ml. The results showed that the ethyl extract of puncture vine plant’s leaves demonstrated promising larvicidal activity, and fatal results were observed where the high rate of mortality was within the 1st larval instar 97.3% and 100% at a concentration(0.5 mg/ml) after 24 and 72 hours exposure respectively, while the lowest mortality rate was within the 4th larval instar 7.4% and 38% at a concentration(0,1mg/ml) after 24 and 72 hours exposure, respectively, also ,it was observed that the leaf extracts modified the morphology of the larval development stage. According to this initial research, those plants are possible alternatives to mosquito larvicide which can be used to produce cost-effective, safe chemicals to control mosquitoes.